Influences of the alcoholic extract of Artemisia annua on gastrointestinal microbiota and performance of Nile tilapia - Soares, Michelly Pereira [UNESP]; Cardoso, Israel Luz [UNESP]; Araújo, Fabrício Eugênio; De Angelis, Carolina Fernandes [UNESP]; Mendes, Rodrigo; Mendes, Lucas William; Fernandes, Marisa Narciso [UNESP]; Jonsson, Claudio Martin; Sonia Claudiado Nascimento de, Queiroz; Duarte, Marta Cristina Teixeira; Rantin, Francisco Tadeu [UNESP]; Sampaio, Fernanda Garcia (Elsevier, 2022)
There is growing interest in strategies for manipulating the gut microbiota of fish for beneficial communities to increase growth, improve lipid metabolism, stimulate the immune response, and improve the physiological state of the gut. We investigated the effects of diets supplemented with an alcoholic extract of Artemisia annua (ae-Aa) on gastrointestinal (GI) microbiota and intestinal morphology along with its effects on the growth performance of the Nile tilapia (Oreochromis niloticus). Juveniles were fed with ae-Aa supplementation (0.00, 0.10, 0.25, and 0.50% in the diets) for 30 days. The different ae-Aa supply levels affected bacterial interactions, resulting in a more complex network and increasing the proportion of positive correlations between bacterial groups. The different amounts of ae-Aa caused variations in specific bacterial abundance. The phyla Fusobacteriota and Bacteroidota were dominant in the intestinal microbiota in all experimental groups. The abundance of bacteria belonging to Fusobacteriaceae, Stenotrophomonas, and Clostridium correlated positively with protein efficiency, specific growth rate, weight gain, and final weight, while the opposite was observed for Acinetobacter. Diets supplemented with 0.25 and 0.5% of ae-Aa increased (p < 0.05) perimeter, height, and thickness of villi, crypt depth, villus:crypt ratio, and number of goblet cells in the intestine of Nile tilapia compared to control group. Nile tilapia supplemented with ae-Aa at all levels improved growth performance (weight gain, specific growth rate, and protein efficiency rate; p < 0.05) and feed conversion ratio (p < 0.05) compared to the control group. The weight gain was about 21% better in supplemented fish with ae-Aa than unsupplemented ones. The ae-Aa supplementation of Nile tilapia for 30 days modulated the GI microbiota communities providing variations in specific bacterial abundance, affecting the bacterial interactions, resulting in a more complex, stable, and connected network while changing their intestinal morphology and improving the performance of the fish.
Keywords: Artemisia; Gastrointestinal microbiota; Growth promoter; Herbal immunostimulants; Intestinal morphology; Natural additives